Impact of novel agent therapies on immune cell subsets and infectious complications in patients with relapsed/refractory multiple myeloma - John, Lukas; Miah, Kaya; Benner, Axel; Mai, Elias K.; Kriegsmann, Katharina; Hundemer, Michael; Kaudewitz, Dorothee; Müller-Tidow, Carsten; Jordan, Karin; Goldschmidt, Hartmut; Raab, Marc S.; Giesen, Nicola (Frontiers in Oncology, 2023)
Infections are a leading cause of morbidity and mortality in patients with multiple myeloma (MM). To examine the effects of modern second-generation novel agent therapy on immune cell subsets, in particular CD4+-T-cells, and infectious complications in patients with relapsed/refractory MM (RRMM), we conducted a prospective cohort study in 112 RRMM patients. Substantially decreased CD4+-T-cells <200/µl before initiation of relapse therapy were detected in 27.7% of patients and were associated with a higher number of previous lines of therapy. Relapse therapy with carfilzomib or pomalidomide showed a significant further decrease of CD4+-T-cells. All novel agents led to a significant decrease of B-cell counts. Overall, infections were frequent with 21.3% of patients requiring antibacterial therapy within the first 3 months of relapse therapy, 5.6% requiring hospitalization. However, in the setting of standard antimicrobial prophylaxis in RRMM patients with very low CD4+-T-cells, no significant association of CD4+T-cell count and an increased risk of infection could be shown. Our findings imply that reduced CD4+-T-cell numbers and infections are common in patients with RRMM. We also demonstrate an association with the number of previous therapies and certain substances suggesting an increased need for personalized prophylaxis strategies for opportunistic infections in this patient cohort.